The radical formula for noncommutative rings - Alkan, M.; Ӧneş O. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 512.5 We determine some classes of left modules satisfying the radical formula in a noncommutative ring. We also show that, under a certain condition, a finitely generated module over an HNP-ring (the generalization of Dedekind domain) both satisfies the radical formula and can be decomposed into a direct sum of torsion modules and extending modules.